Teachers' pass-on practices in whole-class discussions: how teachers return the floor to their students. Issue 4 (1st October 2020) - Willemsen, Annerose; Gosen, Myrte N.; Koole, Tom; de Glopper, Kees
ABSTRACT: This paper reports on a conversation analytic study into the pass-on turns that teachers produce to return the floor to the class following one student's contribution, in the context of whole-class discussions around texts in 4 th grade history and geography lessons. These pass-on turns are remarkable, as the teachers take the turn in order to convey that they will not be responding, but are instead giving their students the opportunity to do so. Our bottom-up analyses allowed us to identify different practices and their projections, and revealed their effects on the ensuing responses. Whereas minimal pass-on practices do not alter the sequential implications of the preceding student turn and typically lead to responses to the student turn, more elaborate practices do slightly alter the sequential implications and mostly lead to responses to the pass-on turn itself, or to an earlier turn produced by the teacher. The analyses show that, although the pass-on turns seem to sustain the Teacher-Student-Teacher-Student participation pattern, this does not hinder the activity of having a whole-class discussion in which students discuss the topic at hand and critically consider and challenge the contributions of their classmates.